New record of species Hygrophila episcopalis R. Ben. (R. Ben.) (Acanthaceae) for the flora of Vietnam - Hai, Do Van; Huyen, Duong Duc (Academia Journal of Biology, 2012)
The genus Hygrophila comprises 100 species in the world and mainly distributed in tropical and subtropical regions. There were 8 species recorded in Vietnam. Specimens of Hygrophila episcopalis (Acanthaceae) have been found in Dak Lak province as a new record for the flora of Vietnam, thus so far, there is a total of 9 species of the genus Hygrophila R. Br. revealed for the flora of Vietnam. Hygrophila episcopalis has some the following characters as: leave shortly petiolate, leaf blade lanceolata to ovate-lanceolata, margin crenulate, both surfaces glandular hairs, based obtuse; inflorescences axillary, often dichasium. The key to species of the genus Hygrophila from Vietnam is also provided. These specimens were collected at Buon Don district in Dak Lak province and are kept in the National Herbarium of the Institute of Ecology and Biological Resources, Hanoi, Vietnam (HN)